Social Media-Based Digital Marketing Management: A Literature Review of Strategies, Challenges, and Opportunities - Erliyani, Ita (Jurnal EMT KITA, 2026)
The rapid growth of social media has driven significant transformations in digital marketing practices and modern marketing management. Social media is no longer used solely as a promotional tool but has evolved into a strategic platform for brand building, consumer engagement, and market expansion, particularly for Micro, Small, and Medium Enterprises (MSMEs). This study aims to systematically review the literature on social media-based digital marketing management by focusing on strategies, challenges, and opportunities faced by organizations. A literature review method was employed by analyzing relevant national and international journal articles. The findings indicate that key strategies widely discussed in the literature include content marketing, engagement-driven strategies, influencer marketing, and data-driven decision-making. Nevertheless, several challenges persist, such as limited digital skills, difficulties in measuring marketing performance, content management constraints, and reputational risks in social media environments. Conversely, opportunities related to market expansion, marketing personalization, social commerce integration, and digital capacity building offer substantial potential for MSMEs. This study contributes to the theoretical development of digital marketing management by synthesizing fragmented research findings and provides practical insights for business practitioners and policymakers in managing social media-based digital marketing more effectively.